1977
DOI: 10.1111/j.1365-3032.1977.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition behaviour of Bracon mellitor, a parasitoid of the boll weevil (Anthonomus grandis)

Abstract: ABSTRACT. The parasitoid, Bracon mellitor, will probe with its ovipositor plant structures containing its host. The identification of methyl parahydroxy‐benzoate (methyl parasept), an antimicrobial additive to the semi‐synthetic diet used for rearing the host, as a releaser of this behaviour prompted an investigation of the parasitoid's response to this chemical. Its absence from field hosts suggested the response was learned. Female parasitoids reared in host‐infested cotton plant buds from the fields or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 24 publications
2
24
1
1
Order By: Relevance
“…Even when there is no attraction for a certain host, this can sometimes be induced by rearing the parasitoid on the host (Thorpe & Jones, 1937). However, it is reported that preadult experience generally has only a minor effect on adult host-searching behaviour, compared to adult experience (Vinson et al, 1977;Sandlan, 1980;Vet, 1983;Drost et al, 1988;Mandeville & Mullens, 1990).…”
Section: Resultsmentioning
confidence: 93%
“…Even when there is no attraction for a certain host, this can sometimes be induced by rearing the parasitoid on the host (Thorpe & Jones, 1937). However, it is reported that preadult experience generally has only a minor effect on adult host-searching behaviour, compared to adult experience (Vinson et al, 1977;Sandlan, 1980;Vet, 1983;Drost et al, 1988;Mandeville & Mullens, 1990).…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, the discovery of learning in parasitoids has provoked thoughts on improvement of natural enemy efficiency through behavioral manipulation (e.g. 50, 78,81,85,119,176,186,199). However, fundamental research on both the behavioral mechanisms underlying inAnnual Reviews www.annualreviews.org/aronline fochemical utilization and the ecological context within which infochemicals and learning are employed has lagged behind.…”
Section: Infochemicals and Pest Managementmentioning
confidence: 99%
“…En effet, les parasites ne sont dans ce cas/t aucun moment en contact avec un 616ment issu des Allium ou de la teigne du poireau, que ce soit au cours de la vie embryonnaire, larvaire, nymphale ou irnaginale, et ils sont cependant aptes, sans exp6rience pr6alable ~i reconnaitre leur h6te habituel.I1 n'y a donc pas ici de conditionnement pr6-imaginal de m~me que chez diverses Drosophiles (Jaenike, 1982). Ceci n'emp~che pas qu'un apprentissage dfi ~ l'exp6rience puisse agir comme ceci a 6t6 d6montr6 chez d'autres esp6ces d'hym6nopt6res parasite (Arthur,1971 ;Vinson et al, 1977;Vet, 1984) et comme le laisse supposer chez D.pulchellus les observations de Labeyrie (1960) sur le comportement des 99 exp6riment6es en pr6sence de morceaux de bas en nylon. Contrairement ~i Nasonia vitripennis (Smith & Cornell, 1979), D. pulchellus parait peu sensible au conditionnement.…”
Section: Discussionunclassified